LABOR AND SOCIO-ECONOMIC CHARACTERISTICS OF STUDENTS OF THE FACULTY OF ACCOUNTING - Chumpitáz Ramos, Domingo Guzmán (2014)
This research work aims to document and provide information to our Authorities, Teachers, Adminis-trative and Student employment and socioeconomic characteristics of the final year students of the School of Accounting Sciences UNMSM-2013. This study has a qualitative approach, descriptive research type. The population were seniors in college. A sample of 186 students was taken, applying stratified sampling. The instrument used was a questionnaire of 36 questions. Results are presented regarding personal and educa-tional characteristics of students, such as gender, age, residence, language, aspects of choice of college and career Accounting. It also has valuable information on labor and economic characteristics of students as if it works currently, income, type of company you work for, as well as their job performance. The main conclusion of the research is the existence of an inde-pendence between work characteristics of the type of occupation and the economic characteristics of the range of wages. Wages of students vary in the type of occupation they perform.